Solvent-Free Synthesis of a Secondary N-Benzhydrylamine as a Chiral Reagent for Asymmetric Deprotonation of Bicyclic N-Benzylamino Ketones - Nodzewska, Aneta; Sidorowicz, Katarzyna; Sienkiewicz, Michal (Synthesis, 2014)
Several chiral secondary N-benzhydrylamines were synthesized in good yields (68–92%) without racemization by the direct alkylation of amines with benzhydryl chloride under solvent-free conditions. Using the solvent-free conditions (R)-N-benzhydryl-1-phenylethylamine was obtained with the highest yield (92%), purified on ion-exchange resin, and converted to its hydrochloride salt. The resulting chiral amine hydrochloride was transformed into lithium amide/lithium chloride mixture used in asymmetric deprotonations of N-benzyl analogues of tropinone and granatanone followed by aldol reactions giving products in high diastereomeric purities (up to 96%) and enantiomeric excesses of 77 to 96%.
Keywords: aldol reaction; N-alkylation; asymmetric synthesis; amines; enantioselectivity